Online film archives: notes on the Chilean university catalogue - Albornoz Fariña, Ignacio (2020)
The present article seeks to provide some tentative insights on the recent constitution of on-line film archives in Chile, paying special attention to the initiatives ―linked to the promotion and diffusion of their collections― developed within the three main universities of the country: The University of Chile, the Catholic University and the State’s Technical University (now USACH). These initiatives will be conceived of as being part of the global frame of “delocalization of contents” and “pixelization of collections”, which will be discussed as consequences of a fundamental turn in archive practices resulting from the irruption of digital technology. Combining empirical cases with theoretical reflections, this article will critically examine and compare the architecture and devices of the different platforms of consultation that these three institutions have made available to users.